Influence of sex on survival rates of HPV-positive oropharyngeal cancers - Preissner, Sally H.; Nahles, Susanne; Preissner, Saskia; Heiland, Max; Koerdt, Steffen (Frontiers in Oncology, 2022)
The role of human papillomavirus (HPV) status for the prognosis of oropharyngeal cancers (OPCs) is discussed controversially. Here, we present an analysis of 144,969 head and neck cancer cases (ICD-10 codes: C00-C13) with a sub-cohort of 62,775 tumor cases of the oropharynx (C01, C09, C10). To this end, de-identified data from electronic health records (EHRs) of about 60 health care organizations from 30 different countries were used. Odds ratios (ORs), hazard ratios (HRs) and Kaplan-Meier analyses were used to compare outcomes between different cancer entities of neoplasms of the base of the tongue (C01), of tonsils (C09) and of the oropharynx (C10) of females and males with and without HPV infection. To avoid the bias from different age-distributions, the cohorts were balanced using propensity score matching. The 5-year survival rate for HPV positive patients is somewhat better than for HPV negative patients but for age- and sex-balanced cohorts there remains no significant advantage for HPV positive patients (HR 1.126 (0.897-1.413). Looking at the different entities and HPV status for age-matched male and female patients separately, HPV is a significantly positive prognostic factor for females in some entities, whereas for male patients it is only a positive prognostic factor for malignant neoplasms of oropharynx (C10) (HR 1.077 (0.602-1.926)).